FDI Determinants in BRICS - Sebastian-Andrei Labes (CES Working Papers, 2015)
In the past two decades the volume of Foreign Direct Investments increased substantially becoming a phenomenon that characterizes the economic environment in the emerging markets. The aim of this working paper is to investigate the Foreign Direct Investments Inflows in the BRICS economies. The research study employs a Panel Data analysis on a sample of 5 countries, the BRICS economies Brazil, Russia, India, China and South Africa and a time series from 1992-2012. The variables taken in consideration are Trade Openness, GDP per capita, Population, Exchange Rate and Human Capital. Our results indicate that the most significant determinants of FDI Inflows are Trade Openness, GDP per capita and Exchange Rate. The value of this work is that it investigates the factors that contribute to the increase of FDI inflows towards the most important emerging economies in the world.
Keywords: F21; O16; P45; 330; FDI; BRICS; emerging economies